Advances on in situ TEM mechanical testing techniques: a retrospective and perspective view - Li, Keqiang; Bu, Yeqiang; Wang, Hongtao (Frontiers in Materials, 2023)
Over the past few decades, in situ transmission electron microscopy (TEM) has emerged as a powerful experimental technique for materials design and characterization. It offers unparalleled dynamic details of materials deformation under mechanical stimuli, providing fundamental insights into their deformation and failure mechanisms for various materials. In this review, we summarize recent advances on in situ TEM mechanical characterization techniques, including classical tension holders, nanoindentation holders, MEMS devices, thermal bimetallic-based techniques, and nanomanipulation techniques. The advantages and limitations of in situ TEM tests are also discussed. To provide a broader perspective, the article highlights promising opportunities for in situ TEM mechanical testing studies in characterization-processing-manufacturing based on nanomanipulation, ultrafast TEM, environmental conditions, data-driven machine learning, and integrated experimental and simulation characterization. This article aims to provide a comprehensive understanding of in situ TEM-based mechanical characterization techniques to promote the development of novel materials with improved mechanical properties for various applications.